N-(Di)icosyl-substituted benzo[a]phenoxazinium chlorides : synthesis and evaluation as near-infrared membrane probes - Naik, Sarala (2011)
Five benzo[a]phenoxazinium chlorides containing alkyl chains with twenty carbon atoms on 5- or 9-positions of the tetracyclic ring were efficiently synthesised and characterised by UV/Vis/NIR spectroscopy. The absorption and emission maxima in ethanol lie in the range 627-641 nm and 645-676 nm, respectively, with quantum yields varying from 0.14 to 0.38. Preliminary photophysical studies with these fluorochromophores in zwitterionic (2,3- bis(palmitoyl-oxy)propyl-2-(trimethylammonio)ethyl phosphate, DPPC) and cationic (N,N-dimethyl-N-octadecyloctadecan-1-aminium bromide, DODAB) vesicles were carried out. The results showed that the new benzo[a]phenoxazinium derivatives are able to detect the gel to liquid-crystalline lipid phase transition through variations, either in the H-aggregation extent or in an acid-base equilibrium.